The Affordable Care Act and its Effects on Trauma Care Access, Short- and Long-term Outcomes and Financial Impact: A Review Article. Issue 1 (1st March 2022) - Newsome, Kevin; Autrey, Cody; Sen-Crowe, Brendon; Ang, Darwin; Elkbuli, Adel
Abstract : Objective: The purpose of this study is to evaluate the current evidence regarding the impact of the ACA on trauma outcomes and the financial impact on trauma patients and trauma systems. Background: Traumatic injuries are the leading cause of death and disability between the ages of 1 to 47 years. Uninsured status has been associated with worse outcomes and higher financial strain. The Affordable Care Act (ACA) was signed into law with the aim of increasing health insurance coverage. Despite improvements in insured status, it is unclear how the ACA has affected trauma. Methods: We conducted a literature search using PubMed and Google Scholar for peer-reviewed studies investigating the impact of the ACA on trauma published between January 2017 and April 2021. Results: Our search identified 20 studies that evaluated the impact of ACA implementation on trauma. The evidence suggests ACA implementation has been associated with increased postacute care access but not significant changes in trauma mortality. ACA implementation has been associated with a decreased likelihood of catastrophic health expenditures for trauma patients. ACA was also associated with an increase in overall reimbursement and amount billed for trauma visits, but a decrease in Medicaid reimbursement. Conclusions: Some improvements on the financial impact of ACA implementation on trauma patients and trauma systems have been shown, but studies are limited by methods of calculating costs and by inconsistent pre-/post-ACA timeframes. Further studies on cost-effectiveness and cost-benefit analysis will need to be conducted to definitively determine the impact of ACA on trauma. Abstract : Mini Abstract: Affordable Care Act implementation has increased access to postacute care for trauma patients, which may improve long-term outcomes. Out-of-pocket expenses and catastrophic health expenditures appear to have decreased significantly and localized disproportionately to lowest- and low-income individuals. Evidence also suggests an increase in the amount billed by trauma centers but not necessarily the amount collected.